Yoga in the Time of Plague – Opportunities and Challenges for Visually Impaired persons to Practice Yoga Online - Albin, Kamila (Virtualizing the lives of people with disabilities, 2021)
This paper discusses yoga practice initiated during lockdown by visually impaired people using information and communication technology. The aim of the analysis is to show what possibilities remote communication tools offer blind and visually impaired people in terms of sport, especially in relation to the practice of yoga. The author reflects on the challenges of mediating exercise and contact with the teacher through digital platforms such as Zoom. The article also uncovers the perspective of yoga teachers who conduct classes with visually impaired people. It addresses the issue of challenges they face in working with this group and new skills in teaching yoga they have had to develop. The author poses the question as to whether this way of practicing yoga can have any advantage over practicing in a yoga school. The author explores answers to the questions posed above using the method of analytical autoethnography. The paper combines different perspectives of insight into the experience of practicing yoga: that of a researcher, a sociologist and a person with disabilities, and that of other people participating in classes and yoga teachers.